PENYULUHAN SAK EMKM BAGI SISWA SMA KATOLIK ST. KRISTOFORUS I- JAKARTA - MF Djeni Indrajati Widjaja (PROSIDING SERINA, 2021)
Business groups can be classified into Micro, Small and Medium Enterprises (MSMEs) and Large (National/Multinational). Each business group has its own accounting standards and tax obligations. This counseling aims to provide a more comprehensive insight for the students of St. Kristoforus I Catholic High School in Grogol, West Jakarta, who generally come from entrepreneurial families. It is hoped that they will be more stable and can help their family business starting from making plans, knowing their rights and obligations as entrepreneurs and other technical matters related to their business accounting records. Accounting Standards for Companies are made according to transaction needs and the broad scope of their business, so that Financial Accounting Standards (SAK) for Micro, Small and Medium Enterprises (MSMEs) are issued under the name Financial Accounting Standards for Micro, Small and Medium Entities, abbreviated as SAK EMKM. The criteria for being an MSME entrepreneur will also be explained. The activity went smoothly considering that it had been prepared and coordinated with the school for this counseling material which would be useful in increasing the knowledge of high school students. This activity is also one of the Tridharma of Higher Education, namely as community service, especially around the Untar campus.